Cytological Profile of Antibacterial FtsZ Inhibitors and Synthetic Peptide MciZ - Araújo-Bazán, Lidia; Ruiz-Avila, Laura B.; Andreu, David; Huecas, Sonia; Andreu, José M. (Frontiers in Microbiology, 2016)
Cell division protein FtsZ is the organizer of the cytokinetic ring in almost all bacteria and a target for the discovery of new antibacterial agents that are needed to counter widespread antibiotic resistance. Bacterial cytological profiling, using quantitative microscopy, is a powerful approach for identifying the mechanism of action of antibacterial molecules affecting different cellular pathways. We have determined the cytological profile on Bacillus subtilis cells of a selection of small molecule inhibitors targeting FtsZ on different binding sites. FtsZ inhibitors lead to long undivided cells, impair the normal assembly of FtsZ into the midcell Z-rings, induce aberrant ring distributions, punctate FtsZ foci, membrane spots and also modify nucleoid length. Quantitative analysis of cell and nucleoid length combined, or the Z-ring distribution, allows categorizing FtsZ inhibitors and to distinguish them from antibiotics with other mechanisms of action, which should be useful for identifying new antibacterial FtsZ inhibitors. Biochemical assays of FtsZ polymerization and GTPase activity combined explain the cellular effects of the FtsZ polymer stabilizing agent PC190723 and its fragments. MciZ is a 40-aminoacid endogenous inhibitor of cell division normally expressed during sporulation in B. subtilis. Using FtsZ cytological profiling we have determined that exogenous synthetic MciZ is an effective inhibitor of B. subtilis cell division, Z-ring formation and localization. This finding supports our cell-based approach to screen for FtsZ inhibitors and opens new possibilities for peptide inhibitors of bacterial cell division.